Beyond the Classroom: A Comprehensive Analysis of Teacher Personality Competence, Parenting Styles, and Their Joint Influence on the Character Formation in Junior High School Education - Rafika Rakhmah; Maria Dominika Niron; Gautam Kumar Jha (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
The formation of students' character is crucial in today's educational landscape for advancing the nation's character. Several factors affecting the formation of students' character include the personality competence of teachers and parental upbringing patterns. This research aims to determine the effect of a teacher's personality competence and parenting styles on the formation of students' character. This study was quantitative research conducted using a survey method. This research population used students from two junior high schools in Sungai Loban District, Tanah Bumbu Regency. The sampling technique used nonprobability sampling with type purposive random sampling. The sample used in this research consisted of 150 students. The sampling technique used was random sampling. Data analysis techniques included descriptive data analysis, data prerequisite testing, and multiple linear regression analysis. The research results indicate a positive and significant effect between teachers' personality competence and parenting styles on forming students' character, resulting in 38.4%. It suggests that the better the teacher's personality competence and the parenting styles implemented by parents, the better the students' character formation.